A resilience cheklist to evaluate coastal dune vulnerabiity - Ramos-Pereira, Ana (2019)
The aim of the proposed resilience checklist is to easily evaluate foredune vulnerability when applied to management. It focus on: (i) the definition of the level of pressure for each use in relation to the foredune resilience threshold, (ii) the direct identification of the system components more vulnerable and (iii) the recognition of management readjustments needed, in order to prevent or minimise impacts. The resilience checklist structure is based on a selection of relevant coastal dune vulnerability descriptors, giving information about the system sensitivity and resilience. All variables selected describe observable signs of foredune degradation or regeneration and are related to system elements susceptible of receiving management intervention. Three major degrees of biophysical vulnerability are recognised: a) Degree 0 - low sensitivity and resilience threshold not exceeded; b) Degree 1 - variable sensitivity and at the resilience threshold; c) Degree 2 - high sensitivity and resilience threshold exceeded. Each degree takes into account the system's level of degradation and the corresponding desirable level of conservation. The application example -Mira's beach southern sector- is a site under a very high summer pressure (seaside recreation and tourism). Three management phases were monitored, between 1996 and 1998. Checklist results show dune management inefficiency and an ineffective sand retention by vegetation as determinants to this foredune site vulnerability and that a planting program is still in need. However, a clear vulnerability decrease in this site was recognised.